Analysis of Creep Test Mixture of Asphalt Concrete Using Flyash for Runway - Anwar Efendy; Ervina Ahyudanari (Jurnal Teknik ITS, 2019)
There are some factors that cause deformation on the runway, such as the pressure of repeated loads caused by large queues of aircraft. The aggregate available in nature has begun to decrease in amount caused considering that infrastructure development in Indonesia continues to increase. Therefore, new material innovations are needed to overcome this, such as the use of flyash as an artificial aggregate of geopolymers in concrete asphalt mixtures. This research was carried out in some tests including Marshall testing which intended to determine the characteristics of artificial aggregate pavement mixtures, using open gradations with specification BBA. Then testing the resistance to deformation (Creep) on the artificial aggregate gradation pavement mixture using the UTM30 Dynapave. Based on the characteristics of the Marshall test the optimum bitumen content value was obtained, with open gradations has OBC value is 6.10%. Results of Creep test (deformation) with load 400 kPa obtained, strain value is 93520 μƐ and stiffness value is 3,998 MPa (sample collapse at cycle 1559 times). It can be concluded that the pavement mixture with open graded artificial aggregate (BBA) has not able to survive deformation.